Regulatory Fit Demonstrates That Prohibitive Voice Does Not Lead to Low Performance Evaluation - Yang, Lu (Frontiers in Psychology, 2020)
Voice behavior, the extra-role behavior of employees based on their sense of responsibility, plays an important role in organizational development. Research shows that an employee’s voice can have a positive impact on both the quality of decision-making and organizational performance. This study explores the relationship between the prohibitive voice and employees’ safety performance based on the theory of regulatory fit. The study examined 372 employees and their leaders in the Ningxia Hui Autonomous Region of China through a questionnaire survey. A moderated model was constructed, and the SPSS-PROCESS was applied to analyze the data. The study results show that prevention regulatory focus fit strengthened the positive association between the prohibitive voice and safety performance evaluation. This study provides a new perspective in understanding leaders’ evaluation of the prohibitive voice and concludes that the prohibitive voice should be encouraged in organizations as it promotes greater adherence to safety measures and helps avoid adverse risks to organizational development.